The adsorption of H2O on K precovered Ni(111) studied by ARUPS and TPD - Bornemann, T.; Steinrück, Hans-Peter; Huber, W.; Eberle, K.; Glanz, M.; Menzel, Dietrich (Surface Science, 1991)
The adsorption of HO on a Ni(111) surface precovered with various amounts of potassium has been studied by TPD, work-function measurements, and angle-resolved UPS using linearly polarized synchrotron radiation. Coadsorption of potassium leads to major changes in the desorption characterics of water which depend strongly on the amount of preadsorbed potassium. At potassium precoverages below θ ≈ 0.14 ML water is molecularly adsorbed; for higher potassium precoverages dissociation of HO into an OH species as well as molecular adsorption is observed at 110 K. The molecularly bound species is significantly stabilized on the surface, as concluded from a high temperature desorption state (170-280 K) in TPD. At low potassium precoverages approximately three HO molecules are affected by one potassium atom. Using symmetry selection rules the symmetry of the adsorbed HO molecules is determined to C(σ), which is probably due to a tilting in the HOH plane. At high potassium precoverages HO decomposes upon adsorption forming an OH species; this OH species is stable up to temperatures above 400 K. The ratio of K to OH formed by dissociation is found to be about 1. From the angle and polarization dependences of the molecular orbitals a tilted orientation of the OH species is derived. The results are compared to those obtained for HO adsorption on clean and oxygen-precovered Ni(111) surfaces, and other alkali/metal systems. © 1991.